Microstructure refinement mechanisms in undercooled solidification of binary and ternary nickel based alloys - Xiaolong Xu; Yongchao Hao; Qi Wu; Ruifeng Dong; Yuhong Zhao; Hua Hou (Journal of Materials Research and Technology, 2023)
Molten glass purification and cycle superheating technologies were used to make Ni65Cu35, Ni65Cu33Co2 and Ni65Cu31Co4 alloys obtain maximum undercoolings of 320 K, 292 K and 300 K respectively. In order to analyze the relationship between morphological characteristics of solidification front and undercooling change during migration of solid–liquid interface, a high-speed camera was used to capture pictures of the recalescence process. Observing the microstructure of the undercooled alloys using metallographic microscope, the characteristics and evolution of microstructure during rapid solidification process of undercooled liquids were analyzed. It was found that grain refinement mechanisms of highly undercooled Ni–Cu–Co alloys was the same as those of the Ni–Cu alloys. Dendrite remelting leads to the grain refinement at low undercooling, while the dominant factor of grain refinement at high undercooling is recrystallization process induced by stress. The internal driving force can be divided into two parts: one is the thermal stress generated by the releasing of solidification latent heat during recalescence process, and the other is the stress and strain accumulated by interaction of liquid flow and primary dendrite during rapid solidification. We also found that addition of third element Co not only played an important role in solidification rate and recalescence effect, but also significantly improved the average hardness of grain refined microstructure, which was about 80% higher than that of as cast alloy. The addition of trace Co was also conducive to the formation of non-segregation solidification microstructure.